Fuzzy logic controller for electronic ballast fluorescent lamp with fiber optic - Moin, Azham Norhezry (2007)
Engineering is concerned with the understanding and controlling the materials and forces of nature for the benefit of mankind. Controllers are devices which create changes, known as system response according to feedback information. Controllers play the critical role of maintaining the desired conditions. Fuzzy techniques have been successfully used in control in several fields, and engineers and researchers are today considering fuzzy logic algorithms in order to implement intelligent functions in embedded systems. This "Fuzzy Logic Controller for Electronic Ballast Fluorescent Lamp with Fiber Optic" is to improve daylight transmission and illumination performance in a building. Presented in the project will use fuzzyTECH-MP Explorer, PIC16F873 and PIC16F84A microcontroller and electronic ballast. A microcontroller is used as it has the advantage of fast design time, no need to design & built interfacing circuits, no compatibility problems, can be interfaced to anything and easy to determined external peripheral timing.